Mengukur Determinan Minat Beli Konsumen Produk Fashion Lokal pada Marketplace Indonesia - Vika Aprianti; Lukman Lukman (Masoem University, 2023)
This study aims to determine the effect of Electronic Promotion and Electronic Word Of Mouth on Buying Intention in Toko Drefaiv followers on the Lazada application. The method used in this research is descriptive with a quantitative research approach. The selection of the sample in this study was carried out using a random sampling technique with a total of 94 respondents. Based on the recap of the research interval, it shows that Electronic Promotion, Electronic Word Of Mouth and Purchase Intention are in the Good category. The results of the multiple correlation correlation between Electronic Promotion and Electronic Word Of Mouth on Buying Interest amounted to 0.778 or 77.8%. This shows that Electronic Promotion and Electronic Word Of Mouth have a strong relationship with Purchase Intention. Partial and simultaneous hypothesis testing also shows that Electronic Promotion and Electronic Word of Mouth have an effect on Interest in buying products at the Drefaiv Store on the Lazada application.